Factors Associated with Cigarettes Use among High School Students in Jakarta - Fauzi, Ridhwan; Areesantichai, Chitlada (Kes Mas: Jurnal Fakultas Kesehatan Masyarakat, 2016)
Background: Tobacco epidemic is in alarming state in Indonesia. More than one-third of people reported as active smoker. The trend of cigarettes use has been vastly growth since past decade particularly among adolescent. The study aims to find out factor associated with cigarettes use among high school students in Jakarta. Method: The study design was cross sectional. A selfadministrated questionare were constructed. A total of 1,318 students from 14 schools all over Jakarta were participated. The data was examined by multiple logistic regressions. Result: The result revealed the prevalence of cigarettes smoking was 21.5% of experimental and 16.2% of past 30 days. Gender, smoking behavior of mother and brother were found as significant predictors of cigarettes smoking. Being male were five times (AOR:5.323, 95% CI:4.143-6.838) more likely to become cigattes smoker than female. The study showed that tobacco use was major public health threat in Indonesia. Conclusion: Government must issue a stronger regulation immediately to reduce tobacco epidemic.